Proceeding International conference and call for paper peaceful life in Islam : local and global challenges - Proceeding_International_conference_and_call_for_paper_peaceful_life_in_Islam... (Language Development Unit ( UPB ) Islamic State College Kudus, 2016)
wt,1/irh,c.1